Wacana Kecantikan Dalam Iklan Pantene: Kajian Kritis Norman Fairclough - Sri W R Situmorang; Elly Prihasti Wuriyani; Malan Lubis (CV. Alim's Publishing, 2024)
Technological advancements and globalization have influenced social structures, including perceptions of beauty standards shaped by the media. This study aims to examine how media shapes beauty standards and its impact on individual perceptions and behavior. The research focuses on the analysis of language and imagery in Pantene shampoo advertisements to understand the underlying ideology and its social impact. A qualitative descriptive method with critical discourse analysis by Norman Fairclough is employed. Data analysis is conducted in detail to uncover the meanings and purposes of the advertisements. The results show that Pantene ads successfully address common hair care issues and present their product as the best solution. The ads build a brand identity that emphasizes strength, beauty, and hair care. Brand ambassadors in the ads are depicted as strong individuals who believe in Pantene’s efficacy, influencing consumer perceptions. Discourse practice analysis reveals that the ads use storytelling, visuals, humor, and everyday language to attract young viewers’ attention. These elements make the ads relevant and appealing, shaping consumer perceptions and behavior. Social practice analysis indicates that the ads reflect societal changes influenced by social media and increased attention to self-care. The ads highlight hair problems due to pollution and offer Pantene as the solution, reflecting the role of advertising in shaping consumer perceptions and actions. The study concludes that Pantene ads successfully build a strong narrative to address hair care issues and establish a brand identity that emphasizes strength, beauty, and hair care. Future research is recommended to examine the long-term impact of these ads on consumer behavior and perceptions.